Significance of Fine Needle Aspiration Cytology in Assessment of Head and Neck Lesions - Patel , Jigna P.; Jansari , Trupti R.; Chauhan , Amit; Jasani , Jasmin (Current Practice in Medical Science Vol. 8, 2022)
The objective of the study was to assess the prevalence and distribution of head and neck swellings diagnosed by Fine Needle Aspiration Cytology (FNAC). To assess the frequency and distribution of various lesion as per the site, age, and gender as well as distribution according to benign and malignant lesion. This was a hospital based, retrospective observational study. Cytomorphology was performed on 544 patients who underwent FNAC for various types of head and neck swellings. The majority of the patients were between the ages of 31 and 40. The majority of the 544 cases' lesions—264—came from the lymph nodes, followed by the thyroid gland (193), the salivary gland (59), the cheek (18), the post-auricular (8), and the forehead/scalp (2). FNAC is a screening and primary diagnostic tool for palpable head and neck lesions that is exceedingly sensitive, specific, and reliable. It supports histology. FNAC aids in directing the therapeutic management by avoiding unnecessary operations and costs for surgical and radiologically decisive purposes, such as whether to resect a benign tumour or to schedule expensive surgeries.